TDO2 Promotes the EMT of Hepatocellular Carcinoma Through Kyn-AhR Pathway - Li, Lei; Wang, Tao; Li, Shanbao; Chen, Zhengqian; Wu, Junyi; Cao, Wanyue; Wo, Qi; Qin, Xuebin; Xu, Junming (Frontiers in Oncology, 2021)
Tryptophan 2,3-dioxygenase (TDO2), an enzyme involved in tryptophan (Trp) metabolism has been linked with some malignant traits of various cancers. Kyn, the main product of Trp metabolism pathway catalyzed by TDO2 and indoleamine 2,3-dioxygenase (IDO) in tumor cells, was also demonstrated to activate aryl hydrocarbon receptor (AhR), which may regulate cancer growth and invasion in some malignancies. However, whether TDO2 participates in the metastasis and invasion of HCC has not been explored before. The underlying mechanism played by TDO2 in this process still requires further investigation. Here, we demonstrated that overexpression of TDO2 correlates with advanced stage or malignant traits in HCC patients. Knockdown or inhibition of TDO2 suppressed the migration and invasion of HCC cells in vitro and in vivo. Epithelial to mesenchymal transition (EMT) is an essential program happened in the initial phase of cancer metastasis. We found that in HCC cells, TDO2 promoted the EMT process evidenced by altered levels of biomarkers for EMT. Mechanically, TDO2 regulated the Kyn production in HCC cell via activated aryl hydrocarbon receptor (AhR). Together, these results indicate that TDO2 promotes the EMT of hepatocellular carcinoma through activating Kyn-AhR pathway, thereby participating in the metastasis and invasion of HCC.